PENGARUH MOTIVASI DAN STRES PEKERJAAN TERHADAP KEPUASAN KERJA DENGAN MEDIASI KOMITMEN ORGANISASIONAL - Lulu Rosemary Dame Sihombing, 11.52.02.0050 (Students Journal of Economic and Management, 2013)
An organization should have wanted for each employee can get the optimal job satisfaction, therefore, it is necessary to improve organizational commitment because of the fact that the organizational commitment can influence job satisfaction. Furthermore, the organizations need to motivate employees and create an environment conducive to reduce job stress as these two variables are really important to reach job satisfaction. This study takes an object of research to employee in PP PAUDNI Regional II Semarang. This research aimed to analyze the effect of motivation to organizational commitment, to analyze the effect of job stress to organizational commitment, to analyze the effect of motivation to job satisfaction, to analyze the effect of job stress to job satisfaction and the last is to analyze the effect of organizational commitment to satisfaction of the employee of PP PAUDNI Regional II Semarang. This study takes an explanatory survey as a method in doing its research. The research sample takes about 112 respondents. The data analysis technique uses descriptive analysis, instrument analysis (validity and reliability), examining the model (regression, F-test, Coefficient of Determination Test), examining the hypothesis (T-test) and examining the mediation effects. The test results in partial motivation give negative influence to organizational commitment. There is an effect of job stress to organizational commitment, motivation gives negative effect to job satisfaction, and job stress gives negative effect to job satisfaction. There is also an effect of organizational commitment to job satisfaction. Mediation results indicate that organizational commitment does not mediate motivation to job satisfaction, but organizational commitment can mediate stress job to job satisfaction. Â Keywords: motivation, job stress, organizational commitment, job satisfaction